Enhanced Tendon-to-Bone Healing of Chronic Rotator Cuff Tears by Bone Marrow Aspirate Concentrate in a Rabbit Model - Liu, Xiao Ning; Yang, Cheol-Jung; Kim, Ji Eui; Du, Zhen Wu; Ren, Ming; Zhang, Wei; Zhao, Hong Yu; Kim, Kyung Ok; Noh, Kyu-Cheol (Clinics in orthopedic surgery, 2018)
To evaluate the influence of bone marrow aspirate concentrate (BMAC) on tendon-to-bone healing in a rabbit rotator cuff model and to characterize the composition of growth factors in BMAC. In this study, 40 rabbits were allocated into five groups: control (C), repair + saline (RS), repair + platelet-rich plasma (PRP; RP), repair + BMAC (RB) and repair + PRP + BMAC (RPB). A tear model was created by supraspinatus tendon transection at the footprint. Six weeks after transection, the torn tendon was repaired along with BMAC or PRP administration. Six weeks after repair, shoulder samples were harvested for biomechanical and histological testing. Ten rabbits were used for processing PRP and BMAC, followed by analysis of blood cell composition and the levels of growth factors . The ultimate load-to-failure was significantly higher in RPB group compared to RS group ( = 0.025). BMAC-treated groups showed higher values of biomechanical properties than RS group. The histology of BMAC-treated samples showed better collagen fiber continuity and orientation than RS group. BMAC contained significantly higher levels of the several growth factors than PRP. Locally administered BMAC enhanced tendon-to-bone healing and has potential for clinical applications.